Corporate venture capital: technological innovation or value creation? A comparative study of CVC- and IVC-invested Chinese listed companies. Issue 3 (2nd September 2019) - Wang, Lei; Zhou, Fangzhao; An, Yunbi; Yang, Jun
ABSTRACT: This paper analyzes the effects of corporate venture capital (CVC) and independent venture capital (IVC) backing on technological innovation and value creation in invested companies. Using data on Chinese listed companies, we show that CVC investment can induce higher firm value than can IVC investment. By considering different dimensions of complementary assets, technological fit, geographical proximity, and product market relations, we explore the mechanism through which CVC contributes to innovation and value creation in invested companies in China.